Foam titanium-based catalytic reaction filter membrane loaded with nano ruthenium-palladium-tin alloy as well as preparation method and application of foam titanium-based catalytic reaction filter membrane

Through the foamed titanium-based catalytic reaction filter membrane supported by nanoruthenium palladium-tin alloy, the problem of low catalytic activity of existing nitrate catalysts is solved, efficient nitrate catalytic reduction and ammonia selectivity are achieved, and good resource treatment effect is achieved.

CN119680536AActive Publication Date: 2025-03-25HUAZHONG NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411871605.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing nitrate catalyst has low catalytic activity and it is difficult to achieve resource utilization of nitrates.

Method used

A foamed titanium-based catalytic reaction filter membrane supported by nano-ruthenium palladium-tin alloy was used to prepare an efficient catalyst by spraying a mixed solution of metal precursor containing ruthenium, palladium and tin on the etched titanium foam surface and soaking it in a reducing agent.

Benefits of technology

The catalytic reduction rate and ammonia selectivity of nitrates are improved, efficient utilization and convenient recycling of catalysts are achieved, and equipment manufacturing costs and operation complexity are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680536A_ABST
    Figure CN119680536A_ABST
Patent Text Reader

Abstract

The invention provides a nano ruthenium-palladium-tin alloy loaded foam titanium-based catalytic reaction filter membrane as well as a preparation method and application thereof, and belongs to the technical field of water treatment. The method comprises the following steps: spraying a metal precursor mixed solution containing ruthenium, palladium and tin on the surface of etched foam titanium to obtain foam titanium containing ruthenium, palladium and tin; the foam titanium containing ruthenium, palladium and tin is soaked in a reducing agent, and the foam titanium-based catalytic reaction filter membrane loaded with the nano ruthenium-palladium-tin alloy is obtained. According to the prepared foam titanium-based catalytic reaction filter membrane, the active metal component loading strength is high, and the catalytic performance is stable; meanwhile, in the related chemical reaction process, formic acid serves as an electron donor to drive the reaction, extra electric energy does not need to be applied, compared with a traditional electrochemical nitrate reduction technology, construction of a complex electrolytic cell is avoided, the manufacturing cost and operation requirements of equipment are greatly reduced, and the method is suitable for industrial production. The method has a wide application prospect in the fields of wastewater denitrification and nitrogen resource recovery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, and in particular to a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy, and a preparation method and application thereof. Background Art

[0002] Nitrogen pollution in the water environment has become a global environmental problem. In many areas, nitrate has become one of the main pollutants in surface water and groundwater due to the large-scale use of nitrogen fertilizers, improper disposal of domestic sewage and nitrogen-containing industrial wastewater. At present, the physical and chemical treatment methods for nitrate wastewater mainly include ion exchange, electrodialysis and reverse osmosis. However, these methods can only separate and enrich nitrates, and cannot reduce nitrates to nitrogen gas to realize the atmospheric nitrogen cycle. In addition, considering that the artificial nitrogen fixation process consumes a lot of fossil energy and produces a lot of carbon emissions, achieving efficient nitrogen recovery is of great significance for the resource utilization of nitrate wastewater.

[0003] Electrochemical nitrate reduction technology is an efficient, simple and easy-to-operate denitrification treatment method: during electrolysis, nitrates obtain electrons on the cathode and are catalytically reduced to ammonia. After the electrolysis is completed, the ammonia can be quickly removed and recovered by using two steps of stripping and absorption. However, for wastewater with low salt content, the cell pressure during electrolysis is often very high, which leads to high energy consumption; not only that, calcium and magnesium ions in the water can also easily deposit on the electrode surface, covering the active sites and causing the electrode activity to decrease. The above unfavorable factors make the implementation of electrochemical nitrate reduction technology easily restricted. Catalytic reduction of nitrates is a process that uses hydrogen as an electron donor to achieve nitrate reduction under the action of a catalyst without the need for power supply and electrode equipment. Compared with the electrochemical reduction method, this catalytic method is more suitable for treating wastewater with low electrolyte concentration or containing calcium and magnesium ions. However, in the traditional nitrate catalytic reduction treatment, the active metal is often loaded onto the powder carrier by impregnation to prepare the catalyst, but this easily causes the active metal to fall off, reduces the catalytic activity, and is not conducive to the recycling of the catalyst. Therefore, the active metal is firmly loaded on the bulk material by high-temperature sintering, which can not only improve the stability of the catalytic activity, but also facilitate the recovery and reuse of the catalyst. In addition, hydrogen, as a flammable and explosive gas, has a high operating risk when used, and its low solubility in water will significantly reduce its utilization rate, resulting in increased wastewater treatment costs. In contrast, formic acid, as a cheap, easy to transport and store industrial product, not only has high reducibility, but more importantly, the decomposition product of formic acid is CO2, which does not bring the risk of secondary pollution. Therefore, it is a more ideal solution to use formic acid as an electron donor in the catalytic reduction of nitrates. Summary of the invention

[0004] The purpose of the present invention is to provide a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy and a preparation method and application thereof, so as to solve the technical problems that the existing nitrate catalyst has low catalytic activity and is difficult to achieve resource processing of nitrate.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy, comprising the following steps:

[0007] 1) spraying a mixed solution of metal precursors containing ruthenium, palladium and tin on the surface of the etched titanium foam under heating conditions to obtain titanium foam containing ruthenium, palladium and tin;

[0008] 2) The foamed titanium containing ruthenium, palladium and tin is immersed in a reducing agent to obtain a foamed titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy.

[0009] Furthermore, the heating temperature is 150-750°C.

[0010] Furthermore, the etching is performed using an oxalic acid aqueous solution, the concentration of the oxalic acid aqueous solution is 1 to 10 wt %, the etching temperature is 50 to 130° C., and the etching time is 1 to 700 min.

[0011] Furthermore, the mixed metal precursor solution containing ruthenium, palladium and tin comprises a ruthenium metal precursor solution, a palladium metal precursor solution and a tin metal precursor solution in equal volume ratios.

[0012] Furthermore, in the mixed solution of metal precursors containing ruthenium, palladium and tin, the ruthenium metal precursor comprises one or more of ruthenium trichloride, ruthenium acetate, ammonium hexachlororuthenate and ruthenium acetylacetonate; the palladium metal precursor comprises one or more of palladium dichloride, chloropalladic acid, sodium chloropalladate, palladium acetylacetonate and palladium nitrate; and the tin metal precursor comprises tin tetrachloride and / or tin dichloride.

[0013] Furthermore, in the titanium foam containing ruthenium, palladium and tin, the loading amount of ruthenium is 0.001-10wt%, the loading amount of palladium is 0.001-15wt%, and the loading amount of tin is 0.001-45wt%.

[0014] Furthermore, the reducing agent comprises one or more of sodium borohydride solution, potassium borohydride solution, dimethylaminoborane solution, lithium aluminum hydride solution and hydrazine hydrate solution, the concentration of the reducing agent is 1 to 1200 mmol / L, and the soaking treatment time is 0.1 to 90 min.

[0015] Furthermore, the titanium content in the titanium foam is ≥85wt%, the pore precision of the titanium foam is 20-90μm, and the thickness is 0.1-3mm.

[0016] The invention also provides a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy.

[0017] The present invention also provides an application of a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy in treating nitrate wastewater. The foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy is installed in a flow cell, and nitrate wastewater added with formic acid flows through the filter membrane, the formic acid is catalytically decomposed and generates electrons, and the nitrate obtains the electrons and is reduced to ammonia;

[0018] The purity of the formic acid is 70-100%, and the molar ratio of the formic acid to the nitrate ion in the nitrate wastewater is 0.1-60:1.

[0019] Beneficial effects of the present invention:

[0020] 1. The present invention adopts formic acid as an electron donor, which avoids the risk of hydrogen leakage in the traditional hydrogen reduction process and greatly reduces the manufacturing cost and operation requirements of the equipment.

[0021] 2. The nano-ruthenium palladium tin alloy of the present invention has excellent formic acid decomposition performance, which helps to improve the catalytic reduction rate of nitrate and ammonia selectivity.

[0022] 3. The present invention adopts high-temperature sintering + chemical reduction to load the nano-ruthenium palladium tin alloy on the foam titanium substrate. The high-porosity foam titanium provides a high surface area, which is beneficial to the fixation and stability of the active metal components.

[0023] 4. The process of placing the titanium foam loaded with nano-ruthenium palladium tin alloy in nitrate wastewater for catalytic reduction achieves efficient utilization and convenient recovery of the catalyst. Compared with the method of directly adding powder catalyst, this method simplifies the operation process and reduces the complexity of the operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the catalytic reaction filter membrane of Example 1 of the present invention;

[0025] Figure 2 This is a transmission electron microscope image of nano-ruthenium palladium tin alloy particles in the catalytic reaction filter membrane of Example 1 of the present invention;

[0026] Figure 3 A schematic diagram of a nitrate reduction process device according to an embodiment of the present invention;

[0027] Figure 4 This is a technical schematic diagram of the nitrate reduction process according to an embodiment of the present invention. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy, comprising the following steps:

[0029] 1) spraying a mixed solution of metal precursors containing ruthenium, palladium and tin on the surface of the etched titanium foam under heating conditions to obtain titanium foam containing ruthenium, palladium and tin;

[0030] 2) The foamed titanium containing ruthenium, palladium and tin is immersed in a reducing agent to obtain a foamed titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy.

[0031] In the present invention, the heating temperature is 150 to 750°C, preferably 200 to 600°C, and more preferably 350 to 450°C.

[0032] In the present invention, the etching is performed using an oxalic acid aqueous solution, the concentration of the oxalic acid aqueous solution is 1 to 10 wt%, preferably 2 to 8 wt%, and more preferably 3 to 6 wt%; the etching temperature is 50 to 130°C, preferably 60 to 120°C, and more preferably 80 to 100°C; the etching time is 1 to 700 min, preferably 100 to 600 min, and more preferably 200 to 400 min.

[0033] In the present invention, the mixed metal precursor solution containing ruthenium, palladium and tin comprises a ruthenium metal precursor solution, a palladium metal precursor solution and a tin metal precursor solution in equal volume ratios.

[0034] In the present invention, the solvents in the ruthenium metal precursor solution, the palladium metal precursor solution and the tin metal precursor solution independently contain one or more of water, ethanol, acetone, acetonitrile, ethylene glycol and isopropanol.

[0035] In the present invention, in the mixed solution of metal precursors containing ruthenium, palladium and tin, the ruthenium metal precursor is preferably one or more of ruthenium trichloride, ruthenium acetate, ammonium hexachlororuthenate and ruthenium acetylacetonate; the palladium metal precursor is preferably one or more of palladium dichloride, chloropalladic acid, sodium chloropalladate, palladium acetylacetonate and palladium nitrate; and the tin metal precursor is preferably tin tetrachloride and / or tin dichloride.

[0036] In the present invention, in the titanium foam containing ruthenium, palladium and tin, the loading amount of ruthenium is 0.001 to 10wt%, preferably 0.1 to 8wt%, and more preferably 0.1 to 6wt%; the loading amount of palladium is 0.001 to 15wt%, preferably 0.1 to 10wt%, and more preferably 0.1 to 8wt%; the loading amount of tin is 0.001 to 45wt%, preferably 0.1 to 30wt%, and more preferably 0.1 to 25wt%.

[0037] In the present invention, the reducing agent comprises one or more of sodium borohydride solution, potassium borohydride solution, dimethylaminoborane solution, lithium aluminum hydride solution and hydrazine hydrate solution, preferably one or more of sodium borohydride solution, potassium borohydride solution and hydrazine hydrate solution; the concentration of the reducing agent is 1 to 1200 mmol / L, preferably 10 to 1000 mmol / L, and more preferably 100 to 800 mmol / L; the immersion treatment time is 0.1 to 90 min, preferably 1 to 80 min, and more preferably 20 to 60 min.

[0038] In the present invention, the titanium content in the titanium foam is ≥85wt%, preferably ≥95wt%; the pore accuracy of the titanium foam is 20-90μm, preferably 30-80μm, and more preferably 40-60μm; the thickness is 0.1-3mm, preferably 1-2mm.

[0039] The invention also provides a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy.

[0040] The present invention also provides an application of a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy in treating nitrate wastewater. The foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy is installed in a flow cell, and nitrate wastewater added with formic acid flows through the filter membrane, the formic acid is catalytically decomposed and generates electrons, and the nitrate obtains the electrons and is reduced to ammonia;

[0041] The purity of the formic acid is 70-100%, and the molar ratio of the formic acid to the nitrate ion in the nitrate wastewater is 0.1-60:1.

[0042] In the present invention, the purity of the formic acid is preferably 80-90%, more preferably 85%; the molar ratio of the formic acid to the nitrate in the nitrate wastewater is 0.1-60:1, preferably 1-50:1, more preferably 10-40:1.

[0043] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] Example 1

[0045] In this embodiment, the titanium foam used has a titanium content greater than 95%, a size of 40 mm×40 mm, a thickness of 1 mm, and a pore accuracy of 50 μm.

[0046] Preparation steps of foam titanium-based catalytic reaction filter membrane:

[0047] 1) The titanium foam was immersed in a 10 wt % oxalic acid solution at 90° C. for surface etching for 150 min. After the etching was completed, the titanium foam was taken out and the surface was rinsed with water.

[0048] 2) Heat the titanium foam to 450°C on a heating table. Dissolve ruthenium trichloride as a ruthenium metal precursor in water, dissolve palladium dichloride as a palladium metal precursor in water, and dissolve tin tetrachloride as a tin metal precursor in ethanol. Subsequently, mix the three solutions in equal volumes and spray them onto the titanium foam surface, ensuring that the temperature is kept constant during the spraying process. The loading amount of ruthenium is 0.01wt%, the loading amount of palladium is 0.1wt%, and the loading amount of tin is 0.1wt%. After spraying, take out the titanium foam and cool it to room temperature.

[0049] 3) Soak the titanium foam in a 500 mmol / L sodium borohydride aqueous solution for 40 minutes. After soaking, take out the titanium foam and rinse the surface with water to obtain a titanium foam-based catalytic reaction filter membrane loaded with nano-ruthenium palladium tin alloy. The scanning electron microscope image of the catalytic reaction filter membrane is as follows: Figure 1 As shown, the transmission electron microscope image of nano-ruthenium palladium tin alloy particles is as follows Figure 2 shown.

[0050] Nitrate catalytic reduction process:

[0051] 1) A certain amount of formic acid (purity of 99.5%) was pre-added to the simulated nitrate-containing wastewater (200 mL, 100.6 mg / L), and the ratio of the formic acid addition concentration to the nitrate molar concentration was 5:1.

[0052] 2) Schematic diagram of the nitrate reduction process Figure 3 As shown: a foam titanium-based catalytic reaction filter membrane 1 is placed in a flow pool 2, and a water pump 3 pumps wastewater from a liquid storage tank 4 into the flow pool 2 at a water flow rate of 40 mL / min. The wastewater then flows through the filter membrane 1 and returns to the liquid storage tank 4. The device operates for 4 hours.

[0053] 3) The technical principle of nitrate reduction process is as follows Figure 4 As shown: when the wastewater flows through the filter membrane, formic acid is catalytically decomposed on the nano-ruthenium palladium tin alloy, releasing electrons; at the same time, nitrate obtains electrons on the nano-ruthenium palladium tin alloy and undergoes a reduction reaction, converting into ammonia.

[0054]

[0055] After the reaction was completed, the results of relevant indicators are shown in Table 1.

[0056] Table 1

[0057]

[0058] The above results show that the foamed titanium-based catalytic reaction filter membrane proposed in the present invention has good nitrate reduction performance, a nitrate removal rate of 87.6%, and an ammonia selectivity of 60.0%.

[0059] Example 2

[0060] In this embodiment, the loading amount of ruthenium is increased from 0.01 wt % to 0.02 wt %, and other conditions remain the same as those in Embodiment 1.

[0061] After the reaction was completed, the results of relevant indicators were shown in Table 2.

[0062] Table 2

[0063]

[0064]

[0065] The above results show that increasing the loading amount of ruthenium helps to significantly improve the nitrate reduction rate and ammonia selectivity, with the nitrate removal rate increased to 98.8% and the ammonia selectivity increased to 100.0%.

[0066] Example 3

[0067] In this example, the loading amount of palladium is increased from 0.1 wt % to 0.15 wt %, and other conditions remain the same as those in Example 1.

[0068] After the reaction was completed, the results of relevant indicators were shown in Table 3.

[0069] Table 3

[0070]

[0071] The above results show that increasing the palladium loading helps to significantly increase the nitrate reduction rate, and the nitrate removal rate is increased to 99.5%, but the change in ammonia selectivity is not obvious.

[0072] Example 4

[0073] In this example, the tin loading is increased from 0.1 wt % to 0.15 wt %, and other conditions remain the same as those in Example 1.

[0074] After the reaction was completed, the results of relevant indicators were shown in Table 4.

[0075] Table 4

[0076]

[0077] The above results show that increasing the tin loading helps to significantly increase the nitrate reduction rate, and the nitrate removal rate is increased to 96.2%, but the change in ammonia selectivity is not obvious.

[0078] Comparative Example 1

[0079] To verify the effect of formic acid, in this comparative example, except that formic acid was not added to the nitrate wastewater, other conditions were consistent with those in Example 1.

[0080] After the reaction is completed, the relevant indicator results are as follows.

[0081] Table 5

[0082]

[0083] In this comparative example, due to the lack of formic acid as an electron donor, the catalytic reduction of nitrate cannot proceed.

[0084] Example 5

[0085] In this embodiment, actual wastewater is used as the treatment object and the treatment water volume is increased. The wastewater comes from the parts pickling workshop of Shanghai Aircraft Manufacturing Co., Ltd. of Commercial Aircraft Corporation of China, which produces high-concentration nitrate wastewater all year round.

[0086] In this embodiment, the titanium foam used has a titanium content greater than 95%, a size of 40 mm×40 mm, a thickness of 1 mm, and a pore accuracy of 50 microns.

[0087] Preparation steps of foam titanium-based catalytic reaction filter membrane:

[0088] 1) The titanium foam was immersed in a 10 wt % oxalic acid solution at 90° C. for surface etching for 150 min. After the etching was completed, the titanium foam was taken out and the surface was rinsed with water.

[0089] 2) Heat the titanium foam to 450°C on a heating table. Dissolve ruthenium trichloride as a ruthenium metal precursor in water, dissolve palladium dichloride as a palladium metal precursor in water, and dissolve tin tetrachloride as a tin metal precursor in ethanol. Subsequently, mix the three solutions in equal volumes and spray them onto the titanium foam surface, ensuring that the temperature is kept constant during the spraying process. The loading amount of ruthenium is 0.05wt%, the loading amount of palladium is 0.2wt%, and the loading amount of tin is 0.2wt%. After spraying, take out the titanium foam and cool it to room temperature.

[0090] 3) Soak the titanium foam in a 600 mmol / L sodium borohydride aqueous solution for 40 minutes. After soaking, take out the titanium foam and rinse the surface with water to obtain a titanium foam-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy.

[0091] Nitrate catalytic reduction process:

[0092] 1) A certain amount of formic acid (purity of 99.5%) was added to nitrate wastewater (200 mL, the water quality of the wastewater is shown in Table 6) in advance, and the ratio of the formic acid addition concentration to the nitrate ion molar concentration was 6:1.

[0093] 2) The operation flow of the nitrate reduction process was consistent with that of Example 1, the water flow rate was 40 mL / min, and the device operation time was 4 hours.

[0094] Table 6

[0095] index Numeric Nitrate concentration (mg / L) 145.9 Ammonia (mg / L) 0.5

[0096] After the reaction was completed, the results of relevant indicators are shown in Table 7.

[0097] Table 7

[0098]

[0099] In this embodiment, for actual nitrate wastewater, the foam titanium-based catalytic reaction filter membrane proposed in the present invention still has excellent nitrate removal efficiency and ammonia selectivity, showing broad application prospects.

[0100] It can be seen from the above embodiments that the present invention provides a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy and its preparation method and application. In the chemical reaction process involved in the present invention, formic acid acts as an electron donor to drive the reaction, and no additional electrical energy is required. Compared with the traditional electrochemical nitrate reduction technology, the present invention avoids the construction of a complex electrolytic cell, greatly reducing the manufacturing cost and operation requirements of the equipment. The present invention shows broad application prospects in the fields of wastewater denitrification and nitrogen resource recovery.

[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy, characterized in that: The following steps are involved: 1) spraying a mixed solution of metal precursors containing ruthenium, palladium and tin on the surface of the etched titanium foam under heating conditions to obtain titanium foam containing ruthenium, palladium and tin; 2) The foamed titanium containing ruthenium, palladium and tin is immersed in a reducing agent to obtain a foamed titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy.

2. The preparation method according to claim 1, characterized in that: The heating temperature is 150-750°C.

3. The preparation method according to claim 1 or 2, characterized in that: The etching is performed using an oxalic acid aqueous solution, the concentration of the oxalic acid aqueous solution is 1-10 wt %, the etching temperature is 50-130° C., and the etching time is 1-700 min.

4. The preparation method according to claim 3, characterized in that: The metal precursor mixed solution containing ruthenium, palladium and tin comprises a ruthenium metal precursor solution, a palladium metal precursor solution and a tin metal precursor solution in equal volume ratios.

5. The preparation method according to claim 4, characterized in that: In the mixed solution of metal precursors containing ruthenium, palladium and tin, the ruthenium metal precursor comprises one or more of ruthenium trichloride, ruthenium acetate, ammonium hexachlororuthenate and ruthenium acetylacetonate; the palladium metal precursor comprises one or more of palladium dichloride, chloropalladic acid, sodium chloropalladate, palladium acetylacetonate and palladium nitrate; and the tin metal precursor comprises tin tetrachloride and / or tin dichloride.

6. The preparation method according to claim 4 or 5, characterized in that: In the titanium foam containing ruthenium, palladium and tin, the loading amount of ruthenium is 0.001-10wt%, the loading amount of palladium is 0.001-15wt%, and the loading amount of tin is 0.001-45wt%.

7. The preparation method according to claim 1, 2, 4 or 5, characterized in that: The reducing agent comprises one or more of sodium borohydride solution, potassium borohydride solution, dimethylaminoborane solution, lithium aluminum hydride solution and hydrazine hydrate solution. The concentration of the reducing agent is 1 to 1200 mmol / L, and the soaking treatment time is 0.1 to 90 minutes.

8. The preparation method according to claim 7, characterized in that: The titanium content in the titanium foam is ≥85wt%, the pore precision of the titanium foam is 20-90μm, and the thickness is 0.1-3mm.

9. The foamed titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy prepared by the preparation method according to any one of claims 1 to 8.

10. The use of the foam titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy according to claim 9 in treating nitrate wastewater, characterized in that: A titanium-based catalytic reaction filter membrane loaded with nano-ruthenium palladium-tin alloy is installed in a flow cell, and nitrate wastewater with formic acid added flows through the filter membrane, where the formic acid is catalytically decomposed and generates electrons, and the nitrate obtains the electrons and is reduced to ammonia; The purity of the formic acid is 70-100%, and the molar ratio of the formic acid to the nitrate ion in the nitrate wastewater is 0.1-60:1.

Citation Information

Patent Citations

  • Preparation and application method of supported bimetallic catalyst for removing nitrate in water

    CN102039125A

  • Nano palladium-silver alloy catalytic material for catalytic reduction of nitrate radicals in water and preparation method and application thereof

    CN107519868A

  • Catalytic reaction filter membrane as well as preparation method and application thereof

    CN118892828A

  • Method for reducing nitrates present in an acid aqueous effluent by catalytic hydrogenation

    WO2001053217A2